Inflammatory breast cancer: a proposed conceptual shift in the UICC–AJCC TNM staging system. Issue 4 (April 2017) - Fouad, Tamer M; Barrera, Angelica M Gutierrez; Reuben, James M; Lucci, Anthony; Woodward, Wendy A; Stauder, Michael C; Lim, Bora; DeSnyder, Sarah M; Arun, Banu; Gildy, Babiera; Valero, Vicente; Hortobagyi, Gabriel N; et al.
Summary: In the absence of histological criteria that distinguish between inflammatory and non-inflammatory breast cancer, diagnosis of inflammatory breast cancer relies entirely on the existence of clinical criteria as outlined by the TNM classification. This classification restricts patients presenting with clinical criteria characteristic of inflammatory breast cancer to subcategory T4d, which immediately relegates all patients with non-metastatic inflammatory breast cancer to stage 3, regardless of tumour size or nodal spread. Patients who present with metastatic disease are consigned to stage 4, and the TNM classification does not distinguish patients on the basis of the presence of inflammatory criteria. Evidence by our group and others suggests that patients with inflammatory breast cancer have significantly reduced overall survival among those who present with distant metastasis at diagnosis (stage 4). In light of these results, this Personal View addresses whether the current TNM staging classification accurately represents a distinction between patients with inflammatory and those with non-inflammatory breast cancer.